Undiagnosed Cases of Human Pneumonia Following Exposure to Chlamydia psittaci from an Infected Rosella Parrot - Anne-Lise Chaber; Martina Jelocnik; Lucy Woolford (Pathogens, 2021)
This report describes two cases of occupational exposure to Chlamydia psittaci following dissection of an infected Rosella (Platycercus elegans). The C. psittaci infections (with one of them resulting in diagnosed pneumonia and hospitalisation) were undiagnosed during routine medical investigations but later established due to epidemiological and clinical evidence, and molecular testing of the archived Rosella’ specimens. This case report stresses the importance of correct application and interpretation of diagnostic tests and the need to raise awareness about this zoonotic pathogen among medical practitioners and people exposed to potential animal carriers. Our findings suggest other infected individuals might be misdiagnosed and that C. psittaci (psittacosis) is likely to be underreported in Australia. This case highlights the need to operationalise the One Health concept. We call for improved communication between human and animal health service providers to allow accurate and rapid diagnosis of this zoonotic disease and raised awareness among medical practitioners. Further targeted surveys of wild birds (and other animals) should be conducted to improve assessment of risks to the general population and people working with or exposed to wild birds.